2021
DOI: 10.3390/bs11030036
|View full text |Cite
|
Sign up to set email alerts
|

School Climate and Responsibility as Predictors of Antisocial and Prosocial Behaviors and Violence: A Study towards Self-Determination Theory

Abstract: Self-determination theory and Vallerand’s hierarchical model have been studied taking into account different types of social factors that can result in different consequences. The purpose of this work was to see if responsibility and social climate could predict antisocial and prosocial behavior and violence. For this, 429 students (M = 11.46, SD = 1.92) participated in the study, answering a questionnaire with five variables: school climate, responsibility, motivation, satisfaction of psychological needs, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
(42 reference statements)
2
11
0
4
Order By: Relevance
“…Taking SDT as a reference and in line with Vallerand's hierarchical model, it can be observed that applying hybrid methodologies that manipulate social factors, such as responsibility, are suitable for producing an improvement in basic psychological needs and promoting a more self-determined motivation [19], generating positive consequences at an affective and emotional level, such as enjoyment and the intention to be physically active, in line with the studies by Manzano-Sánchez et al [54], Menéndez-Santurio and Fernández-Río [90], and Merino-Barrero et al [24].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Taking SDT as a reference and in line with Vallerand's hierarchical model, it can be observed that applying hybrid methodologies that manipulate social factors, such as responsibility, are suitable for producing an improvement in basic psychological needs and promoting a more self-determined motivation [19], generating positive consequences at an affective and emotional level, such as enjoyment and the intention to be physically active, in line with the studies by Manzano-Sánchez et al [54], Menéndez-Santurio and Fernández-Río [90], and Merino-Barrero et al [24].…”
Section: Discussionsupporting
confidence: 66%
“…Within the SDT framework, we find Vallerand’s hierarchical model of intrinsic and extrinsic motivation [ 52 ], which establishes that social factors, such as responsibility [ 53 , 54 , 55 ], can be considered as a trigger for the satisfaction of basic psychological needs (autonomy, competence, and relatedness) that in turn promote a more self-determined motivation in students [ 56 ], and generate positive consequences at the cognitive, affective, and behavioral levels [ 24 ], related to well-being. In this way, the hybridization of TPSR and TGfU is intended to foster student responsibility and promote a more self-determined motivation achieving greater health-related benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The current findings emphasized the effect of a motivational climate on responsibility. Similarly, Manzano-Sánchez et al (2021) found that responsibilities were positively related to school climate and prosocial behaviors and negatively related to antisocial behaviors and violence. The researchers (Biddle et al, 2019) indicate that if the experience and context of physical activity are positive, the outputs will be positive (e.g., self-esteem).…”
Section: Methodsmentioning
confidence: 94%
“…O bien, valorando la responsabilidad como desencadenante de conductas mediante la secuencia de Vallerand, destacando la existencia del estudio de Merino-Barrero et al (2019), donde se predijo la deportividad, la intención de ser físicamente activo y el estilo de vida saludable. Por otro lado, el estudio de Manzano-Sánchez et al (2021), viéndose el poder predictivo de la responsabilidad y el clima social Escolar sobre las Conductas Prosociales, la Violencia y las Conductas Antisociales. No encontrándose estudios que hayan abordado la resiliencia como desencadenante ni como consecuente.…”
Section: Teoría De La Autodeterminaciónunclassified